2014
DOI: 10.2109/jcersj2.122.393
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect between TiO<sub>2</sub> and ubiquitous metal oxides on photocatalytic activity of composite nanostructures

Abstract: We studied photocatalytic activity of highly porous nanotubular TiO 2 films modified with nanoclusters of ubiquitous metal (Ti, Al, Zn, Sn, Cu, W) oxides prepared by chemical bath deposition and atomic layer deposition as well as nanoclusters of metal rich suboxides and mixed titania suboxides prepared by atomic layer deposition by following decomposition of methylene blue under simulated solar light. The mixed titania suboxide clusters constructed on the surface of TiO 2 nanotubes by atomic layer deposition d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 19 publications
1
16
0
Order By: Relevance
“…Using this approach, they managed to obtain non-stoichometric suboxides strongly attached to tube walls. Eventhough in their paper, SEM details are not shared, the photocatalytic activity of as-prepared composites is significantly higher compared to plane TiO 2 nanotubes [74], as shown in Fig. 3.16.…”
Section: Atomic Layer Depositionmentioning
confidence: 94%
See 3 more Smart Citations
“…Using this approach, they managed to obtain non-stoichometric suboxides strongly attached to tube walls. Eventhough in their paper, SEM details are not shared, the photocatalytic activity of as-prepared composites is significantly higher compared to plane TiO 2 nanotubes [74], as shown in Fig. 3.16.…”
Section: Atomic Layer Depositionmentioning
confidence: 94%
“…The second paper by Turkevych and coauthors [74] has recently reported on the synergic effect between TiO 2 nanotubes and ubiquitous metal oxides on the photocatalytic activity of composite nanostructures, as depicted in Fig. 3.16c.…”
Section: Atomic Layer Depositionmentioning
confidence: 98%
See 2 more Smart Citations
“…The effective utilization of ALD for deposition of various materials within TiO 2 nanotube layers has been demonstrated e.g. for oxides [26][27][28][29][30] and sulfides [31,32], yielding interesting synergic effects. Even though the use of the ALD to deposit Pt nanoparticles on various catalytic supports has been reported in previous works [33][34][35], no reports show an effective deposition of Pt nanoparticles within high aspect ratio 1D TiO 2 tubular nanostuctures.…”
Section: Introductionmentioning
confidence: 99%